Nitric Oxide and Prostacyclin Are Involved in Antithrombotic Action of Captopril in Venous Thrombosis in Rats - Pawlak, Robert; Chabielska, Ewa; Golatowski, Janusz; Azzadin, Arsalan; Buczko, Włodzimierz (Thrombosis and Haemostasis, 1998)
The long-term administration of captopril to patients with a left ventricular dysfunction after myocardial infarction reduces the rate of recurrent coronary thrombosis. Thus, in the present study we investigated the influence of angiotensin-converting enzyme inhibitors (ACE-Is) on experimental venous thrombosis in normotensive rats and the involvement of NO and PGI2 in this effect. Animals were treated with captopril (1.5, 5 or 25 mg/kg twice daily, CAP), enalapril (15 mg/kg once daily, ENA) or distilled water for 10 days, per os. After ligation of the vena cava the thrombus weight decreased in both CAP and ENA treated rats. The effect was most pronounced in animals given the highest dose of CAP (p<0.0001 vs. control) and was significantly stronger than observed in ENA treated animals (CAP vs. ENA p<0.01). The mean blood pressure measured by the “tail cuff” method and platelet aggregation were not altered by either of the ACE-Is. The antithrombotic activity of CAP was reduced by indomethacin (2.5 mg/kg, s.c.) and independently by the NO-synthase inhibitor NG-nitro L-arginine methyl ester (3 mg/kg i.v. bolus + 3 mg/kg/h i.v. infusion, L-NAME). In the latter case CAP regained its antithrombotic properties in rats pretreated with L-Arginine (300 mg/kg i.v. + 300 mg/kg/h i.v.) before administration of L-NAME (p<0.05 vs. control). Moreover, the concomitant administration of indomethacin and L-NAME failed to completely abolish the antithrombotic action of captopril. Similar effects were observed in respect to the incidence of venous thrombosis. Our study documents a novel and important effect of ACE-Is on the vein thrombotic process and demonstrates the involvement of NO and PGI2 in this phenomenon.